2017
DOI: 10.1038/cr.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Mettl3-/Mettl14-mediated mRNA N6-methyladenosine modulates murine spermatogenesis

Abstract: Spermatogenesis is a differentiation process during which diploid spermatogonial stem cells (SSCs) produce haploid spermatozoa. This highly specialized process is precisely controlled at the transcriptional, posttranscriptional, and translational levels. Here we report that N-methyladenosine (mA), an epitranscriptomic mark regulating gene expression, plays essential roles during spermatogenesis. We present comprehensive mA mRNA methylomes of mouse spermatogenic cells from five developmental stages: undifferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
331
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(344 citation statements)
references
References 71 publications
12
331
1
Order By: Relevance
“…In the zebrafish embryos with METTL3 deficiency, hematopoietic stem cells cannot be produced as usual (Ear & Lin, ). METTL3‐/METTL14‐mediated mRNA N 6 ‐methyladenosine modulates murine spermatogenesis (Lin et al, ).…”
Section: The Biological Functions Of M6amentioning
confidence: 99%
“…In the zebrafish embryos with METTL3 deficiency, hematopoietic stem cells cannot be produced as usual (Ear & Lin, ). METTL3‐/METTL14‐mediated mRNA N 6 ‐methyladenosine modulates murine spermatogenesis (Lin et al, ).…”
Section: The Biological Functions Of M6amentioning
confidence: 99%
“…RNA modifications can influence pre-mRNA splicing, mRNA export, turnover, and translation, which are controlled in the male germline to ensure coordinated gene expression [35]. Recent works have shown that m6A depletion in mice dysregulates translation of transcripts that are required for spermatogonial proliferation and differentiation [34]. Moreover, m 5 C modifications have been shown to be essential for transmission of diet-induced epigenetic information across generations in the epididymis [53].…”
Section: Testis-specific Rmps Are Mainly Expressed During Meiotic Stamentioning
confidence: 99%
“…It is well established that mRNA levels do not always correlate well with protein levels [59]. Thus, to assess whether our findings would hold at the protein level, we performed immunohistochemistry in both testis and epididymis to characterize the expression patterns of 4 RMPs at the protein level: (i) NSUN7, a putative m 5 C methyltransferase that has been shown to affect sperm motility [56,60]; (ii) NSUN2, an m 5 C tRNA methyltransferase involved in sperm differentiation [61]; (iii) METTL14, a component of the m 6 A methyltransferase complex, which has been shown to be dynamically regulated during spermatogenesis [34], and (iv) HENMT1, a piRNA 2'-O-methyltransferase responsible for transposon silencing during spermatogenesis [5] (Figure 3D, see also Figure S3E).…”
Section: Immunohistochemistry Reveals Heterogeneity In Rmp Expressionmentioning
confidence: 99%
“…Spermatogenesis is a complex and orderly biological process that depends on a precisely controlled cascade of diverse genes regulating germ cell proliferation (Lin et al, ; Wang et al, ). To produce mature male gametes, chromosomal reduction during division produces a haploid genome in each daughter cell and this is followed by morphological differentiation of these cells, which leads to the formation of mature sperm (Loveland et al, ).…”
Section: Introductionmentioning
confidence: 99%